Cellular traits regulate fluorescence-based light-response phenotypes of coral photosymbionts living in-hospite - McQuagge, Audrey; Pahl, K. Blue; Wong, Sophie; Melman, Todd; Linn, Laura; Lowry, Sean; Hoadley, Kenneth D. (Frontiers in Physiology, 2023)
Diversity across algal family Symbiodiniaceae contributes to the environmental resilience of certain coral species. Chlorophyll-a fluorescence measurements are frequently used to determine symbiont health and resilience, but more work is needed to refine these tools and establish how they relate to underlying cellular traits. We examined trait diversity in symbionts from the generas Cladocopium and Durusdinium, collected from 12 aquacultured coral species. Photophysiological metrics (ΦPSII, σPSII, ρ, τ1, τ2, ABQ, NPQ, and qP) were assessed using a prototype multi-spectral fluorometer over a variable light protocol which yielded a total of 1360 individual metrics. Photophysiological metrics were then used to establish four unique lightresponse phenotypic variants. Corals harboring C15 were predominantly found within a single light-response phenotype which clustered separately from all other coral fragments. The majority of Durusdinium dominated colonies also formed a separate light-response phenotype which it shared with a few C1 dominated corals. C15 and D1 symbionts appear to differ in which mechanisms they employ to dissipate excess light energy. Spectrally dependent variability is also observed across light-response phenotypes that may relate to differences in photopigment utilization. Symbiont cell biochemical and structural traits (atomic C:N:P, cell size, chlorophylla, neutral lipid content) was also assessed within each sample and differ across light-response phenotypes, linking photophysiological metrics with underlying primary cellular traits. Strong correlations between first-and second-order traits, such as Quantum Yield and cellular N:P content, or light dissipation pathways (qP and NPQ) and C:P underline differences across symbiont types and may also provide a means for using fluorescence-based metrics as biomarkers for certain primary-cellular traits.